PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN MELALUI MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING DI INDONESIA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Estrella Febyani; Devie Devie Devie (Business Accounting Review, 2017)
The purpose of this study was to examine the effect of managerial ownership on firm value with earning management as intervening variable (the study  of the companies listed on the Indonesia Stock Exchange in 2011-2015). The population in this study are all  go public’s companies that issued annual report and listed on Indonesia Stock Exchange in 2012 until 2014. Sampling technique used to take the sample in this study is non-profitability sampling. The type of sampling used in this study is purposive sampling that the determination of the sample considering certain criteria that have been determined against the object of research in accordance with the purpose of the study. Data analysis tool used in this research is descriptive analysis and multiple regression analysis. The result of this research are: (1) managerial ownership have significant effect to firm value, (2) managerial ownership have significant effect to earnings management, and (3) earnings management have significant effect to company value.